Kangaroo Method according to Ecosystem Thought (Research, Society and Development, 2021)
Objective: Bringing together the Kangaroo Method and Ecosystem Thinking. Methodology: Descriptive, qualitative and theoretical reflection study, carried out from April to August 2021. For theoretical foundation about the Kangaroo Method, the Technical Manual of the Kangaroo Method was used and, in relation to Ecosystem Thinking, a search was carried out in the databases International Literature on Health Sciences and Latin American and Caribbean Literature on Health Sciences with the descriptors “Thought” and “Ecosystem”, in addition to the manual search of bibliographical references in Google Scholar. The detailing of the information collected from the articles was carried out through an instrument that contained the title and main perspectives of the Ecosystem Thoughts. For the analysis and synthesis of the articles, a synoptic table was created containing the information described above and the Kangaroo Method assumptions to promote the approximation between the themes. Results: Through the actions developed in the Kangaroo Method, it was possible to see an approximation with the Ecosystem Thinking through comprehensive care; interconnection and contextualization of services; vision of totality/unity; interconnection, integrality, interaction, mutual influences, cooperation and interdependence among all components; holistic and systemic view; and particularities of space and environment. Final Considerations: The study evidenced the approximation of Ecosystem Thoughts in the Kangaroo Method, incorporating care to the newborn in a comprehensive, individualized, humanized, holistic and quality way.